THE LEVEL OF DAMAGE AND THE IDENTIFICATION OF MELOIDOGYNE SPP. FROM MAHANG BARU VILLAGE, HULU SUNGAI TENGAH, SOUTH KALIMANTAN - Fitriyanti D.; Hayati A. (Russian Journal of Agricultural and Socio-Economic Sciences)
This study was conducted to address the lack of information regarding celery crop damage in South Kalimantan due to Root Knot Nematode (RKN). This study is critical for determining the extent of celery plant damage caused by RKN (Meloidogyne spp.) in numerous districts/cities in South Kalimantan and identifying the Meloidogyne species discovered. The purposive sampling of celery crop infected with RKN was conducted in one city and three districts in South Kalimantan. Sampling was conducted at Sukamaju Ujung village, Landasan Ulin Utara, Banjarbaru City; Mandiangin village, Banjar Regency; Hamak Village, Telaga Langsat District, Hulu Sungai Selatan Regency and Jamil, Banyu Jaranih and Mahang Baru Villages, Labuan Amas Selatan District, Hulu Sungai Tengah Regency. The result showed that RKN were discovered in the Sukamaju Ujung and Mahang Baru villages. Sukamaju Ujung was the most heavily attacked by RKN, with high damage levels ranging from 85-90%, a high galling index of 8-9, and the greatest population of 1282 nematodes/5 grams of roots. In Mahang Baru village, RKN was found to have a damage level of only 15% but a high galling index of 8 (eight) and population of 1049 nematodes/5 grams of roots. Based on the perineal pattern of adult females, three species of Meloidogyne were found in Mahang Baru village, namely M. javanica, M. incognita, and M. arenaria. These three species had previously been found in Sukamaju Ujung village.